Kembalikan Baliku Community’s Concept of Janger Semara Ratih Dance and the Interest of Jakarta’s Young Generation - Permata, Faizha Dyah; Trisnawati, Ida Ayu; Sustiawati, Ni Luh (Journal of Aesthetics, Creativity and Art Management, 2024)
This research was conducted to examine the concept of the Janger Semara Ratih dance work which aims to attract the interest of visitors to the Indonesia Kaya Gallery, especially the younger generation. This research was conducted using qualitative methods. This was carried out in an interview process with the Janger Dance choreographer Semara Ratih, founder of the Kembalikan Baliku Community. Apart from that, data can also be obtained from recordings of the Janger Semara Ratih dance, choreographer interviews from several media and supporting books that match the focus of the discussion. The traditional art of Balinese dance is still very popular among the younger generation, especially in the city of Jakarta, Indonesia. There is a dance community in Jakarta, founded three years ago which presents a dance performance entitled Janger Semara Ratih. This dance work has been performed at an annual event namely Indonesian Cultural Heritage and also at regular events at the Indonesia Kaya Gallery. The Janger Semara Ratih dance work was performed by several dancers who are members of the Kembalikan Baliku Community. This performance is presented to attract the interest of the younger generation in Jakarta to help preserve Balinese dance arts by providing story concepts related to the lives of today's young people.